Implementation of the CIPP evaluation model in Indonesian nursing schools - Yakobus Siswadi; Grace Solely Houghty; Triulan Agustina (Jurnal Ners, 2019)
Introduction: The implementation of the Indonesian National Nursing Competency Test (INNCT) has faced several challenges, especially related to the low pass rate. The pass rate has decreased over time, but the number of examinees has increased. The aim of this study was to evaluate the nursing schools’ performance in INNCT using the Context Input Process Product (CIPP) evaluation model.Methods: A quantitative description was used in this study. The Performance Evaluation of Nursing Program Questionnaire based on CIPP was developed and used to collect the data.  The participants in this study were faculty members and alumni from the nursing schools that were a member of AINEC within region V. The variables of this study were the nursing school pass rate and the school’s performance.Results: 320 participants were involved in this study. The passing rate of the nursing school in INNCT was in the moderate category. The CIPP evaluation shows that out of the four aspects, there were two (2) aspects, namely “context and input” that were in the category of having met the requirements and two (2) aspects, namely “process and product”, were in the category exceeding the requirements.Conclusion: Nursing schools have fulfilled the government regulation based on the CIPP evaluation and the nursing schools need to make a strategic plan to improve their performance and to increase their pass rate in INNCT.